Rutin and quercetin content in the forage of common buckwheat as affected by maturity and conservation method. (20th March 2017) - Mariotti, Marco; Andreuccetti, Victoria; Nuvoloni, Roberta; Gatta, Domenico; Liponi, Gian Battista; Pedonese, Francesca; Fratini, Filippo; Turchi, Barbara; Saccomanni, Giuseppe; Torracca, Beatrice
Abstract: The content of rutin and quercetin was examined in fresh, hayed and ensiled forage of common buckwheat. The treatments were two varieties of buckwheat, 'Bamby' and 'Lileja', and two ripening stages of harvest, first green and first brown achenes. In the silage, produced with experimental mini‐silos, additional treatments were the wilting of the forage (at 35% dry matter) and the addition of Lactobacillus plantarum as inoculum. The concentration of rutin and quercetin decreased between ripening stages. Flavonoid content was different among varieties, 'Lileja' had the highest rutin concentration (about 20 g kg −1 ), while 'Bamby' had the highest quercetin concentration (about 0.2 g kg −1 ). Rutin and quercetin yield reached about 70 kg ha −1 and 500 g ha −1, respectively. The haymaking process reduced the rutin and quercetin concentration in the forage, however, the extent of reduction was higher at the green (−43% for rutin and −55% for quercetin) than at the brown achenes stage (−13% rutin and −26% quercetin). The ensiling process, with the associated bacterial activities, led to the transformation of rutin into quercetin. The decrease of rutin in the silage, compared to fresh forage, ranged between −84 and −99%, while in contrast, the quercetin concentration increased by about 140–200 times. However, the loss of total rutin plus quercetin during ensiling was limited (approximately 5%). Forage wilting negatively affected rutin transformation in quercetin, while bacterial inoculum improved it. These results highlight that the forage of buckwheat could be considered like a dietary supplement rich of flavonoids, with the potential to be used as functional feed* .